HLA-DQB1 Allele and Hypocretin in Korean Narcoleptics with Cataplexy - Jeong, Jong-Hyun (The Korean Academy of Medical Sciences, 2007)
Cataplexy is one of the most pathognomonic symptoms in narcolepsy. This study was designed to investigate the frequency of the HLA-DQB1 allele and cerebrospinal fluid (CSF) hypocretin levels in Korean narcoleptics with cataplexy as compared with those who do not have cataplexy. Seventy-two narcoleptics were selected based on polysomnography and multiple sleep latency test as well as their history and clinical symptoms at Sleep Disorders Clinic. The patients were divided into a narcolepsy with cataplexy group (n=56) and a narcolepsy without cataplexy group (n=16). All patients were subjected to HLA typing to determine the frequency of DQB1 allele and to spinal tapping to measure the level of CSF hypocretin. In cataplexy-positive patients, as compared with cataplexy-negative patients, the frequency of HLA-DQB1*0602 was found to be significantly high (89.3% vs. 50.0%) (p=0.003). On the other hand, the frequency of HLA-DQB1*0601 was found to be significantly low (0% vs. 43.8%) (p<0.001). In 48 of 56 cataplexy-positive patients (85.7%), hypocretin levels were decreased (≤110 pg/mL). However, only 6 of 16 cataplexy-negative patients (37.5%) exhibited a decreased hyopcretin level (p<0.001). The high frequency of HLA-DQB1*0602, low frequency of HLA-DQB1*0601 and low hypocretin levels in cataplexy-positive groups suggest that cataplexy-positive narcolepsy might be an etiologically different disease entity from the cataplexy-negative.